(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Many thinkers and critics from Plato, Aristotle Horace through Aquinas and Dante to Hegel, Marx. Freud and Derrida have viewed literature in broad cultural context. Perhaps the most conventional definition of the word Culture” refers to the beliefs, rituals and practices of a given social or ethnic group or nation Kamala Markandaya, a pioneer member of the Indian Diaspora occupies an outstanding place among the Indian women novelists writing in English. Cross-cultural and inter-racial conflicts are the recurring theme in her novels. The present paper aims at depicting the cultural conflict in various novels of Kamala Markandaya. The theme of East- West Encounter is presented in the context of rural vs urban Indian in Nectar in a Sieve. Tannery stands for modernisation of rural India. Western way of life is depicted in Some Inner Fury. A Silence of Desire depicts conflict between traditionalism and modernity.